From malaria control to elimination in South Africa: The researchers' perspectives - Khumbulani W. Hlongwana; Joyce Tsoka-Gwegweni (AOSIS, 2016)
Background: Global decline in malaria episodes over the past decade gave rise to a debate to target malaria elimination in eligible countries. However, investigation regarding researchers' perspectives on barriers and facilitating factors to effective implementation of a malaria elimination policy in South Africa (SA) is lacking. Aim: The aim of this study was to investigate the malaria researchers' knowledge, understandings, perceived roles, and their perspectives on the factors influencing implementation of a malaria elimination policy in SA. Setting: Participants were drawn from the researchers who fulfilled the eligibility criteria as per the protocol, and the criteria were not setting-specific. Methods: The study was a descriptive cross-sectional survey conducted through an emailed self-administered semi-structured questionnaire amongst malaria researchers who met the set selection criteria and signed informed consent. Results: Most (92.3%) participants knew about SA's malaria elimination policy, but only 45.8% had fully read it. The majority held a strong view that SA's 2018 elimination target was not realistic, citing that the policy had neither been properly adapted to the country's operational setting nor sufficiently disseminated to all relevant healthcare workers. Key concerns raised were lack of new tools, resources, and capacity to fight malaria; poor cross-border collaborations; overreliance on partners to implement; poor community involvement; and poor surveillance. Conclusion: Malaria elimination is a noble idea, with sharp divisions. However, there is a general agreement that elimination requires: (a) strong cross-border initiatives; (b) deployment of adequate resources; (c) sustainable multistakeholder support and collaboration; (d) good surveillance systems; and (e) availability and use of all effective intervention tools.